Coupling Ratio-Based Design and Seismic Performance of Modular Prefabricated Hybrid Coupled Walls - Yun Shi; Yumin Zhang; Jianbo Dai; Guangyuan Weng (Advances in Civil Engineering)
Based on the advantages of modular prefabricated multistory steel structure, a full-bolt-connected modular steel coupling beam-hybrid coupled wall system is presented. Further, a method of estimating the coupling ratio (CR) is proposed according to the continuous link method. A CR-based seismic design procedure is determined such that the structure utilizes the lateral stiffness of the shear wall, which is necessary to avoid structural damage under frequently occurring earthquakes. However, it also exhibits excellent ductility of the coupling beams, which is necessary for dissipating energy under infrequent earthquakes. Subsequently, nonlinear hysteretic analyses are conducted from finite element analysis software ABAQUS, and a parametric study based on the finite element technique is performed to identify the optimal value of the coupling ratio. Results indicate that the seismic performance of modular prefabricated HCWs was excellent, and the basic requirements for ductile behavior and lateral stiffness were satisfied for CR values from 50% to 60%. The obtained results confirm the accuracy of the CR-based seismic design method proposed in this study and are supported by the selection of the design parameter at the initial design stage.